Monitoring of hysteretic friction degradation of curved surface sliders through a nonlinear constrained estimator. (1st January 2021) - Calabrese, A.; Gandelli, E.; Quaglini, V.; Strano, S.; Terzo, M.; Tordela, C.
Highlights: A technique for monitoring the hysteretic friction degradation of CSSs is presented. A nonlinear constrained approach is employed. An estimator design model is derived. Demonstrated effectiveness by means of experimental data. Abstract: The lack of validated physical models concerning the degradation of the coefficient of friction of sliding isolators induced from the heating of the sliding surfaces during the seismic motion hampers the interpretation of experimental data and the formulation of accurate numerical models. An estimator based on a Constrained Unscented Kalman Filter (CUKF), suitable for real-time monitoring, combined with a Random Walk Model approach (RWM) which identifies the friction degradation function without the a priori knowledge of a physical model and ensuing analytical law has been developed in the study. Both numerical analyses and experimental tests of a 2 DOF shear-type physical model are employed to demonstrate the validity of the technique. The proposed estimator is able to provide an accurate estimation of the state of the system, by predicting the structural displacement histories, and to identify the hysteretic degradation function in different friction conditions, from low to high friction.